Myocardial changes in incident haemodialysis patients over 6-months: an observational cardiac magnetic resonance imaging study. Issue 1 (December 2017) - Rutherford, Elaine; Mangion, Kenneth; McComb, Christie; Bell, Elizabeth; Cockburn, Samantha; Talle, Mohammed; Roditi, Giles; Welsh, Paul; Woodward, Rosemary; Radjenovic, Aleksandra; Struthers, Allan; Jardine, Alan; et al.
Abstract Patients commencing on haemodialysis (HD) have an increased risk of cardiovascular events in the first year after starting HD compared to those patients established on HD longer. Left ventricular (LV) hypertrophy and abnormal myocardial strain predict mortality. There may be changes in the myocardium of incident HD patients over a 6-month period of HD which may explain changes in cardiovascular risk. We used CMR to consider changes in LV mass, myocardial strain and T1 mapping. We examined changes in pre-dialysis highly sensitive troponin T. 33 patients undergoing HD for <12 months were recruited. Participants underwent CMR at baseline and after 6-months of standard care. 6-months of HD was associated with reduction in LV mass index (Baseline: 78.8 g/m2 follow up: 69.9 g/m2, p = <0.001). LV global longitudinal strain also improved (Baseline: −17.9%, follow up: −21.6%, p = <0.001). Change in T1 time was not significant (Baseline septal T1 1277.4 ms, follow up 1271.5 p = 0.504). Highly sensitive troponin T was lower at follow up (Baseline 38.8 pg/L, follow up 30.8 pg/L p = 0.02). In incident HD patients, 6-months of HD was associated with improvements in LV mass, strain and troponin. These findings may reflect improvement in known cardiac tissue abnormalities found in patients over the first year of HD.